Association of Prenatal Maternal Depression and Anxiety Symptoms With Infant White Matter Microstructure. Issue 3 (March 2019) - Dean, Douglas C.; Planalp, Elizabeth M.; Wooten, William; Kecskemeti, Steven R.; Adluru, Nagesh; Schmidt, Cory K.; Frye, Corrina; Birn, Rasmus M.; Burghy, Cory A.; Schmidt, Nicole L.; Styner, Martin A.; Short, Sarah J.; et al.
Abstract : (Abstracted from JAMA Pediatr 2018;172(10):973–981) Depression and anxiety are common during pregnancy. These disorders are estimated to affect 7% to 20% of pregnant women; however, many women reach only a subclinical threshold and are not formally diagnosed.